2012
DOI: 10.1128/jcm.00603-12
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Streptococcus pyogenes in Pleural Fluid Samples from Pediatric Patients with Empyema

Abstract: A total of 120 pleural fluid specimens from 113 pediatric patients were tested using two rapid antigen detection assays for Streptococcus pyogenes. Results were compared to culture, Gram stain, and PCR results. Each rapid antigen assay detected 9 out of 10 (90%) PCR-positive samples, with 100% specificity. These antigen detection assays are useful to provide microbiological diagnosis of empyema caused by S. pyogenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Our study also confirms the usefulness of molecular assays and other techniques such as the rapid antigen test for diagnosing GAS in pleural effusion, especially when antibiotics have been given before admission 13 14 . Emm genotypes were identified in less than half of the GAS strains isolated.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our study also confirms the usefulness of molecular assays and other techniques such as the rapid antigen test for diagnosing GAS in pleural effusion, especially when antibiotics have been given before admission 13 14 . Emm genotypes were identified in less than half of the GAS strains isolated.…”
Section: Discussionsupporting
confidence: 79%
“…The microbiological diagnosis of GAS empyema was based on the identification of GAS in pleural fluid (culture, GAS rapid antigen test13 or 16S rRNA PCR sequencing14) or in a blood culture. The microbiological diagnosis of S. pneumoniae empyema was based on the identification of S. pneumoniae in pleural fluid (culture, pneumococcal soluble antigen, 16S rRNA PCR sequencing or S. pneumoniae -specific PCR) or in a blood culture.…”
Section: Methodsmentioning
confidence: 99%
“…All these data confirmed that RADTs designed for GAS pharyngitis can be used to diagnose extrapharyngeal GAS infection accurately. A single study on 120 pleural fluid samples but limited to 10 GAS-positive specimens from pediatric patients has already been published (17). Sensitivities of 100%, 90%, and 10% have been reported for GAS PCR, RADTs, and culture, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care rapid antigen tests for sore throat, that recognise the carbohydrate group antigen of S . pyogenes , can be adapted for use in iGAS infection 6 , 7 but thus far no protein-based targets have been identified.…”
Section: Introductionmentioning
confidence: 99%